2013
DOI: 10.5732/cjc.012.10222
|View full text |Cite
|
Sign up to set email alerts
|

Műllerian duct anomalies and their effect on the radiotherapeutic management of cervical cancer

Abstract: Radiotherapy plays a major role in the treatment of cervical cancer. A successful radiotherapy program integrates both external beam and brachytherapy components. The principles of radiotherapy are strongly based on the anatomy of the organ and patterns of local and nodal spread. However, in patients with distorted anatomy, several practical issues arise in the delivery of optimal radiotherapy, especially with brachytherapy. Müllerian duct anomalies result in congenital malformations of the female genital trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Considering the high incidence of cervical carcinoma worldwide, the absolute number of cervical carcinomas in patients with genitourinary malformation might be expected to be very high, especially in less developed regions. However, the opposite is true, as the number of reported cases is low 5. This may be because the incidence of cervical carcinoma in developed countries is very low; moreover, many less developed regions are less likely to be able to afford imaging prior to surgery or radiotherapy, resulting in a missed diagnose of genitourinary malformations.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the high incidence of cervical carcinoma worldwide, the absolute number of cervical carcinomas in patients with genitourinary malformation might be expected to be very high, especially in less developed regions. However, the opposite is true, as the number of reported cases is low 5. This may be because the incidence of cervical carcinoma in developed countries is very low; moreover, many less developed regions are less likely to be able to afford imaging prior to surgery or radiotherapy, resulting in a missed diagnose of genitourinary malformations.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been estimated that as many as 5% of cervical cancer patients may have undetected malformations. With many cases of cervical cancer diagnosed and treated in economically disadvantaged areas where CT and MRI imaging are not readily available (and as such are not required by FIGO for staging), the true incidence of those with a coexisting uterine anomaly and cervical cancer may be underreported [ 14 ]. Most are treated with surgical approaches when feasible, due to anatomic difficulties in managing these patients from a radiotherapeutic perspective [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…With many cases of cervical cancer diagnosed and treated in economically disadvantaged areas where CT and MRI imaging are not readily available (and as such are not required by FIGO for staging), the true incidence of those with a coexisting uterine anomaly and cervical cancer may be underreported [ 14 ]. Most are treated with surgical approaches when feasible, due to anatomic difficulties in managing these patients from a radiotherapeutic perspective [ 14 ]. Our review of the literature revealed only 2 cases of cervical cancer in women with congenital anomalies of the female reproductive tract treated with definitive radiotherapy with cervical BT as a component of treatment [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…A transverse vaginal septum resulting from defects in vertical fusion may be associated [9,13]. According to the American Fertility Society (AFS) classification, uterus didelphys belongs to the Class III, which includes malformations arising from complete absence of fusion of the two Mu¨llerian ducts [9,[12][13][14].…”
Section: Embryologymentioning
confidence: 99%